Global supply chain pressures, international trade, and inflation - Julian Di Giovanni; Sebnem Kalemli-Ozcan; Álvaro Silva; Muhammed Ali Yildirim (Federal Reserve Bank of New York, 2022)
We study the impact of the COVID-19 pandemic on euro area inflation and how it compares to the experiences of other countries, such as the United States, over the two-year period 2020-21. Our model-based calibration exercises deliver four key results: (1) compositional effects, or the switch from services to goods consumption, are amplified through global input-output linkages, affecting both trade and inflation; (2) inflation can be higher under sector-specific labor shortages relative to a scenario with no such supply shocks; (3) foreign shocks and global supply chain bottlenecks played an outsized role relative to domestic aggregate demand shocks in explaining euro area inflation over 2020-21; and (4) international trade did not respond to changes in GDP as strongly as it did during the 2008-09 crisis despite strong demand for goods. These lower trade elasticities in part reflect supply chain bottlenecks. These four results imply that policies aimed at stimulating aggregate demand would not have produced as high an inflation as the one observed in the data without the negative sectoral supply shocks.
Keywords: E2; E3; E6; F1; F4; 330; inflation; international trade; supply chains; spillovers; Coronavirus; Eurozone; Inflation; Inflationskonvergenz; Internationale Wirtschaftsbeziehungen; Lieferkette; Spillover-Effekt; Außenhandel; Konsumentenverhalten; Arbeitsangebot; Welt